2018
DOI: 10.1016/j.pedneo.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the diagnosis of neonatal sepsis by measuring interleukins: A systematic review

Abstract: Neonatal sepsis is a dangerous and common disease among infants which is associated with high morbidity and mortality. Interleukins may be helpful for diagnosis of neonatal sepsis. Therefore, this study is conducted to investigate the role of interleukins in the diagnosis of neonatal sepsis. In this study, databases including PubMed, Cochrane Library, ISI and Google Scholar were searched up to 2016. Keywords were: Sepsis, neonatal, interleukins, prediction and diagnosis. Study inclusion criteria were: Articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…In one study, positive result for CSF culture was reported in 36.88% (7). In another study, the prevalence of neonatal meningitis was 1% (22).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, positive result for CSF culture was reported in 36.88% (7). In another study, the prevalence of neonatal meningitis was 1% (22).…”
Section: Discussionmentioning
confidence: 94%
“…In one study, K. pneumoniae, Coagulase negative staphylococci, and Enterococcus faecalis were the most common bacterial pathogens (28). In the study of Samiee Rad et al (2012), the most common pathogens were E. coli, K. pneumoniae, Enterobacter, Pseudomonas aeruginosa and Staphylococcus aureus (22). Several mechanisms have been described for neonatal meningitis, but primary septicemia and then the secondary distribution in cerebrospinal fluid is the most common underlying issue (38).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it could be possible to be related to a gene for sepsis [11]. A systemic fetal cytokine response, defined as a plasma interleukin-6 (IL-6) value above 11 pg/m is considered a major independent risk factor, such as fetal inflammatory response syndrome (FIRS), a diagnostic marker of early-onset neonatal sepsis (EONS) and a risk predictor of white matter injury (WMI) [12].…”
Section: Universidad De Manizales -Facultad De Ciencias De La Saludmentioning
confidence: 99%
“…On the other hand, concentrations of IL-6 have also been determined [20] during the microbial invasion of the amniotic cavity (MIAC) and amniotic fluid after delivery, and they evaluated the presence of acute histological chorioamnionitis (ACH) in the placenta. They also observed a greater intra-amniotic inflammatory response, which was mediated by IL-6 concentrations.…”
Section: Distribution Of Newborn Sex Risk Factors Sepsis and Intermentioning
confidence: 99%
“…Bacterial culture is considered the gold standard for the diagnosis of NS, but it takes 1 to 2 days to obtain the examination results with low sensitivity (4). In addition, several biological markers with high sensitivity have been identified, including interleukins (ILs), C-reactive protein (CRP), micro-erythrocyte sedimentation rate and procalcitonin (PCT) (5)(6)(7). However, the clinical application of these indicators is limited due to their poor specificity.…”
Section: Introductionmentioning
confidence: 99%